Odpowiedzi

2010-02-09T13:52:13+01:00
A) 3(a-2)=3a-6
b) -4(x+y)=-4x-4y
c) -5(-x+1)=5x-5
d) -3a(⅓-a)=-a+3a²
e) (t-2s-1)*7=7t-14s-7
f) ½(2a-4b+1)=a-2b+1/2
g) m(2m+3)=2m²+3m
h) 3p(2r+5p-1)=6pr+15p²-3p
i) xy(2x-3y+5)=2x²y-3xy²+5xy
4 4 4
2010-02-09T13:56:57+01:00
A) 3(a-2)=3a+(-6)
b) -4(x+y)=-4x+(-4y)
c) -5(-x+1)=5x+(-5)
d) -3a(⅓-a)=-1,5a+3akwadrat
e) (t-2s-1)*7=7t+(-14s)+(-7)
f) ½(2a-4b+1)=a+(-2b)+1/2
g) m(2m+3)=2mkwadrat +3m
h) 3p(2r+5p-1)=6pr+15pkwadrat +(-3p)
i) xy(2x-3y+5)=2xkwadraty +(-3xykwadrat)+5xy
2 3 2
2010-02-09T14:25:45+01:00
A) 3(a-2)= 3*-a+2
b) -4(x+y)=-4*-x-y
c) -5(-x+1)=-5*x-1
d) -3a(⅓-a)=-3*a*-⅓+a
e) (t-2s-1)*7=(t-2*s-1)*7
f) ½(2a-4b+1)= ½*-2*a=4*b-1
g) m(2m+3)=m*-2*m-3
h) 3p(2r+5p-1)=3*p*-2*r-5*p+1
i) xy(2x-3y+5)=x*y*-2*x+3*y-5
1 2 1